ICT in the Teaching/Learning Process of Natural Sciences at the Universities of Trujillo State - Venezuela: A Study of Indicators - Lobo, Hebert; Ramón Rosario, Jesús; Materán, Iris; Pacheco, Ana; Morón, Francisco; Ruiz, Lidia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
Considering the hypothesis that the integration of ICT in Venezuelan universities, especially to the process of teaching/ learning, curricula or teaching practices, it has not been rapid, uniform, stable and satisfying, this research wasconducted to determine the current state of progress in its incorporation through multiple channels, means and resources that constitute the higher education institutions of Trujillo state, according to a set of indicators. In this descriptive research, are explored by a design field, from the Manual for the Measurement of Information Technology and Communication in Education Institute for Statistics (2009) and according to the vision derived by Sunkel (2006), consultant to the Economic Commission for Latin America and the Caribbean (ECLAC), the following categories of indicators: (a) policy and strategy, (b) infrastructure and access, (c) Training of teachers (d) Integration into the curriculum and (e) students learning. The results indicate significant misalignments in the process, that correlate with the type of institution, the attitude and training of teachers and students, as well as deficiencies in infrastructure and technology resources.